Gas Hydrate Dissociation Events During LGM and Their Potential Trigger of Submarine Landslides: Foraminifera and Geochemical Records From Two Cores in the Northern South China Sea - Huang, Yi; Cheng, Jun; Wang, Mingmin; Wang, Shuhong; Yan, Wen (Frontiers in Earth Science, 2022)
Although submarine slope failures and occurrence of gas hydrates are well known in the Dongsha area of the South China Sea (SCS), the causal relationship between the aforementioned phenomena has not been clearly understood yet. Herein, we present carbon and oxygen isotope compositions of benthic foraminifera and sulfur isotopic composition of chromium reducible sulfur (CRS; δ34SCRS) from two cores from the Dongsha slope, aiming at identifying gas hydrate dissociation events. The geochemical data indicated that a large amount of gas hydrate dissociated at the beginning of the Last Glacial Maximum (LGM). Meanwhile, disturbances in the sedimentary strata indicated that a submarine landslide occurred at the end of the LGM. Moreover, the associated abrupt increase of benthic foraminifera abundance implies that the submarine landslide was probably caused by an intense methane release from gas hydrate dissociation. A smaller scale submarine landslide related to gas hydrate dissociation was also recorded in core 973-5, retrieved from the flat area at the base of the slope.